Assessment of hydride precipitation modelling across fuel cladding: Hydriding in non-defective and defective fuel rods. (August 2023) - Feria, F.; Herranz, L.E.
Highlights: Extension of in-clad hydrogen precipitation modelling of HYDCLAD model. The extension better predicts the hydride rim formed in the cladding. The extension is capable of estimating hydrides blisters in defective rods. The variability of the solubility limits hardly impacts the hydrides distribution. Abstract: This work studies the effect of the hydrogen precipitation on the in-clad hydrides distribution, given its potential impact on cladding integrity (ductility reduction). To do so, a hydrogen migration/precipitation model derived, called HYDCLAD, has been extended to take into account two different options for the precipitation modelling: a semi-empirical approach and a more phenomenological one. The model has been further extended to encompass the variability of existing solubility limits. Different scenarios of hydrogen uptake have been assessed from non-defective and defective irradiated fuel rods. In the first case, the comparison with data allows concluding that the more phenomenological approach better predicts the hydride rim if a re-parameterization is done along with the oxidation front effect modelled in HYDCLAD. In defective fuel rod, the enhancement with the more phenomenological approach is capable of estimating the hydrides blisters expected under massive hydrogen uptake in the cladding fuel side. The variability of the solubility limits hardly has an impact on hydrides distribution.